Aerial view of Dow Chemical Company Research Center - Dow Chemical Company (1964)
Aerial view of the Dow Chemical Company Research Center located in Midland, Michigan. Various buildings are numbered and identified as follows on the back of the photograph: 1) Library, Patent and Research Administration 2) Biochemical Research Laboratory 3) Administration Offices, Nuclear and Basic Research Lab. 4) Chemicals Research Laboratory 5) Chemical Physics Research Laboratory 6) Radiochemistry Research Laboratory 7) Polymer Research Laboratory 8) Electrochemical and Inorganic Research Laboratory 9) Biochemical Testing Laboratory 10) Highway and Construction Materials Laboratory 11) Computations Research Laboratory 12) Nuclear and Basic Research Laboratory
Keywords: Research institutes; Aerial views; Dow Chemical Company; Aerial photographs